PSVII-13 Effect of polyunsaturated fatty acid and methionine supplementation during late gestation on offspring duodenal amino acid and peptides transporters in sheep. (30th November 2020) - Rosa-Velazquez, Milca; Batistel, Fernanda; Relling, Alejandro E
Abstract: The intestine plays a crucial role in nutrient digestion and absorption, and its function is critical for animal growth and health. However, the effect of maternal nutrition on offspring's intestine is not well documented. The objective of this study was to evaluate the effect of supplementing polyunsaturated fatty acids (PUFA), methionine (M) or both to ewes during late gestation on offspring duodenal amino acid (AA) and peptides transporters. Twenty-four post-weaned lambs (6/treatment) born from ewes supplemented from day 100 (d100) gestation until lambing were used. Dam supplementation was: 1) no PUFA or M supplementation (CONT, NFA-NM); 2) supplementation with PUFA (PUFA-NM, 1 % StrataG113); 3) a source of M (NFA-MET, 0.1 % rumen protected methionine, Smartamine); and 4) PUFA and MET (PUFA-MET). At weaning (60 days of age) lambs were placed in 24 pens and fed a common finishing diet for 56 days. On d56, lambs were harvested and samples of the duodenum were collected to quantified amino acid (AA) and peptides transporters. Protein quantification of amino acid transporters was performed using Simple Western System. Offspring data was analyzed as a 2x2x2 factorial (FA, M, and sex). No triple interaction was found (P > 0.15). Dam supplementation did not affect SLC38A2 and SLC38A10 expression. A trend was observed in MET*Sex interaction (P = 0.1), M-ewes and NM-wethers had a greater SLC6A19 expression compared with NM-ewes and M-wethers. Furthermore, SLC7A5 protein expression tended to decrease (P = 0.1) in M-ewes and NM-wethers when compared with M-wethers. There was an effect of FA supplementation, PUFA born animals had a greater SLC38A1 protein expression when compared to NFA born offspring. Maternal supplementation of M or PUFA led to a modification in the protein expression of duodenal AA transporters, and this modification could be influenced by the sex of the offspring.